Shatta Music, from Madinina to The World: New Identity Dynamics in Martinique - Coraline Kandassamy (Études Caribéennes)
This article investigates the rise of Shatta music since 2013. The music genre which originated from Jamaican Dancehall riddims, gained popularity through the support of West Indian communities during carnival and parties. Today, the genre has evolved into a means of expression for Black French Caribbean youth. This study explores the cultural elements that contributed to the development of Martinican Shatta music and analyzes its growth. Overall, the research aims to examine how Shatta music has become a representation of a new identity in Martinique, between local and global processes.